The effect of photomultiplier tube glass entrance window on plastic scintillator case sheet photon dosimetry: a monte carlo study - Nurul Syazwina, Mohamed; Suffian, Mohamad Tajudin; A. Aydın, . (2019)
Plastic scintillators are commonly used for medical dosimetry due to the density and effective atomic numbers that are closer to human soft tissue. When a photomultiplier tube (PMT) is used with a thin scintillator, reflected photon and electrons as a result of Compton scattering either inside the scintillator or PMT entrance window, might contribute to a significant source of additional absorbed dose. Monte Carlo simulation was used to study the effect of different PMT window materials on the absorbed dose of a 0.5 mm plastic scintillator cast sheet for parallel photon beam energy up to 1 MeV. The additional dose in the plastic scintillator from 400 keV to 1 MeV due to sapphire and LiF glass are increases from 11 % to 47 % and 8 % to 31 %, respectively. Despite of the lower density of Quartz among other materials, Quartz and MgF2 demonstrate almost similar trends of additional dose throughout the energies, which is closer to the sapphire. This may due to relatively low effective atomic number and density of LiF, and hence producing less reflected dose. To reduce the unexpected additional dose, a plastic scintillator with a considerable thickness of a PMT window should be adopted for the ‘soft-tissue’ dose response.